The Outcome of Single Stage versus Two Stage Repair in Anorectal Malformations with Recto-Vestibular Fistula - Shafiq-Ur-Rehman, Muhammad Riaz-Ul-Haq, Zarlish Fazal, Yasir Makki, Muhammad Anwar, Fareena Ishtiaq, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Imperforate anus with recto-vestibular fistula is one of the most common anorectal malformations in females. Wound infection and disruption after recto-vestibular fistula repair may affect the fecal continence and functional outcome. Fecal incontinence may cause long term social, economical and psychological problems in children. Although a protective colostomy reduces the infectious complications and dehiscence, it is also associated with many problems. Aim: To compare the safety, feasibility, post operative complications and functional outcomes of limited posterior sagittal anorectoplasty with or without colostomy. Study design: Prospective descriptive study. Place and duration of sudy: Department of Pediatric Surgery, Sahiwal Teaching Hospital Sahiwal, from 1st January 2019 to 31st December 2021. Methodology: Forty-one patients with congenital recto-vestibular fistula were managed by two techniques. Patients were divided into two groups. Group A (19 patients): were operated by single stage limited posterior sagittal anorectoplasty without covering colostomy. Group B (22 patients): were operated by two stage technique. Limited posterior sagittal anorectoplasty and covering colostomy in first stage and stoma closure was done in second stage. The patients in both groups were evaluated for hospital stay, operation time, postoperative complications, fecal continence, constipation, bowel function. Results: The age of patients ranged from 11-56 months (mean 26.93 months) in Group A and 9-60 months (mean 27.03 months) in Group B. The total length of hospital stay in Group A ranged from 7-11 days (mean 9.20 days); however, in Group B, it ranged from 4-6 days (mean 5.01 days) for first stage procedure and 8-11 days (mean 9.27 days) for second stage colostomy closure procedure. In Group A, complications were, wound infection 03 (15.78%), anal stenosis 02 (10.52%), mucosal prolapse 01 (5.26%), constipation 04 (21.05%), soiling 04 (21.05%), perineal excoriation 03 (15.78%) and recurrent H-type recto-vestibular fistula 01 (5.26%). In Group B, during the first stage of repair, one patient (4.54%) developed wound infection. Mucosal prolapse was observed in one patient (4.54%). Constipation was reported in 03 (13.63%) and soiling in 01 (4.54%). Peri stoma skin excoriation was seen in five patients (22.72%). Stomal prolapse was observed in two patients (9.09%). Two patients (9.09%) developed wound infection after colostomy closure. Conclusion: Single stage repair of congenital recto-vestibular fistula increases the risk of postoperative complications. Two stage approach is associated with less postoperative complications. However it is associated with lengthy hospital stay, long operation time and complications related to stoma formation and closure. Keywords: Recto-vestibular fistula, Limited posterior sagittal anorectoplasty, Single stage technique, Two stage technique.